IDENTIFIKASI TUMBUHAN ANTIDIABETES BERDASARKAN ANALISIS KUANTITATIF ASAM TANAT - ', Trina; ', Fitmawati; Sofiyanti, Nery (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Diabetes mellitus is a condition where the blood glucose is higher than normal condition. This condition will damage tissues in human body, and is usually caused by free radicals or by the decrease of the antioxidant defence activity. Tannic acid (tannin) is a member of antioxidant and antidiabetic agents. Antidiabetic plants used by the people are commonly unknown about their amount of tannic acid content. This study was aimed to investigate antidiabetic plants by analyzing its tannic acid content quantitatively. These compounds were compared with commercial antidiabetic drug. The determination of total tannic acid content in the plants was conducted using Folin Ciocalteu method. The results showed that the tannic acid consisted of antidiabetic drug, jackfruit bark, gambier sap, raru bark, jengkol bark, capo leaf, and sipait leaf with concentration of 21.01, 29.98, 40.95, 51.01, 51.84, 59.70 and 60.16 mg/g, respectively. The tannic acid content in the six antidiabetic plants were higher than those of commercial antidiabetic drug, therefore all of the tested plants is potential as antidiabetic drug.